Degradation of Methylene Blue by Hot Electrons Transfer in SnSe - Li Fan; Xin Su; Hongliang Zhu; Hao Liu; Shuai Lou; Yi Shi; Shancheng Yan (Advanced Materials Interfaces, 2023)
Abstract The thermoelectric effect allows for the direct generation of potential gradients from the temperature gradient of the material, and this spontaneous formation of cathodes and anodes can greatly facilitate chemical reactions. Here, the thermoelectric conversion process of SnSe, which has proven to be the best thermoelectric material, and its catalytic effect in the degradation of methylene blue are studied. With excellent thermoelectric properties but no heavy metals contained, it is revealed that SnSe serves as a thermal catalyst for organic degradation. By manifestation of the UV absorption, the degradation efficiency of methylene blue is greatly enhanced with the help of SnSe as a catalyst, especially at high temperatures. By thermoelectric test and theoretical analysis, it is further demonstrated that the non‐equilibrium carriers of SnSe at high temperatures create a built‐in electric field along the temperature gradient, thereby contributing to electron transport during the degradation of methylene blue. These results show that SnSe has an outstanding degradation effect on methylene blue, providing a new pathway for the degradation of water pollution.